Mencari Pembiayaan Pendidikan dengan Mengaplikasikan SD-Preneur - Wakhudin; Beny Wijarnako; Cahyono Purbomartono (PT FORMOSA CENDEKIA GLOBAL, 2022)
This community service aims to find solutions to the financing difficulties faced by education units, especially in primary schools. Building SD-Preneur is expected to be the answer, so that schools have financial flexibility in carrying out school programs. The service method begins with the socialization of SD-Preneur, implementation, monitoring, and evaluation. SD-Preneur, which started at SD Muhammadiyah Cipete, Cilongok, Banyumas, Central Java, February 4, 2022, raised the spirit of entrepreneurship comprehensively, by dividing the school into two rooms: a non-profit education room and a business room. With SD-Preneur, SD Muhammadiyah Cipete does not only rely on education financing from students, but from businesses such as catering, textile products, and even from banking.